알럼 및 철수산화물 흡착제의 광산배수 내 비소 흡착성능 비교연구 - 최궁원(Kung-Won Choi); 박성숙(Seong-Sook Park); 강찬웅(Chan-Ung Kang); 이준학(Joon Hak Lee); 김선준(Sun Joon Kim) (자원환경지질, 2021)
Since the mine reclamation scheme was implemented from 2007 in Korea, various remediation programs have been decontaminated the pollution associated with mining and 254 mines were managed to reclamation from 2011 to 2015. However, as the total amount of contaminated mine drainage has been increased due to the discovery of potential hazards and contaminated zone, more efficient and economical treatment technology is required. Therefore, in this study, the adsorption properties of arsenic was evaluated according to the adsorbents which were derived from water treatment sludge(Alum based adsorbent, ABA-500) and granular ferric hydroxide(GFH), already commercialized. The alum sludge and GFH adsorbents consisted of aluminum, silica materials and amorphous iron hydroxide, respectively. The point of zero charge of ABA-500 and GFH were 5.27 and 6.72, respectively. The result of the analysis of BET revealed that the specific surface area of GFH(257 m2·g-1) was larger than ABA-500(126~136 m2·g-1) and all the adsorbents were mesoporous materials inferred from N2 adsorption-desorption isotherm. The adsorption capacity of adsorbents was compared with the batch experiments that were performed at different reaction times, pH, temperature and initial concentrations of arsenic. As a result of kinetic study, it was confirmed that arsenic was adsorbed rapidly in the order of GFH, ABA-500(granule) and ABA-500(3mm). The adsorption kinetics were fitted to the pseudo-second-order kinetic model for all three adsorbents. The amount of adsorbed arsenic was increased with low pH and high temperature regardless of adsorbents. When the adsorbents reacted at different initial concentrations of arsenic in an hour, ABA-500(granule) and GFH could remove the arsenic below the standard of drinking water if the concentration was below 0.2 mg·g-1 and 1 mg·g-1, respectively. The results suggested that the ABA-500(granule), a low-cost adsorbent, had the potential to field application at low contaminated mine drainage. 2007년부터 국내 광해방지기본계획이 추진되어 광해발생 광산에 대한 광해방지사업이 진행되어 왔으며 2011년부터 2015년까지 254개 광산에서 발생된 광해를 처리 및 복구하였다. 그러나 추가적인 광해 발생 발견으로 오염갱내수 유출량이 지속적으로 증가함에 따라 보다 효율적이고 경제적인 처리기술이 요구되고 있다. 따라서 본 연구에서는 정수처리장의 슬러지 폐기물을 활용해 제조한 알럼 슬러지 흡착제(Alum based adsorbent, ABA-500)와 과립상 철수산화물 흡착제(Granular ferric hydroxide, GFH)를 광산배수 내 오염물질인 비소를 대상으로 각각의 흡착특성을 비교 및 분석했다. 이들 흡착제의 주요 구성 성분은 각각 알루미늄/규소 계열의 광물과 비정질 철수산화물이었다. 고형첨가방법으로 흡착제의 영전하점을 분석한 결과 ABA-500, GFH 각각 pH 5.27, 6.72에서 표면전하량이 0이 되었다. BET 분석을 통한 질소 등온 흡탈착 결과 세 흡착제 모두 메조기공이 발달해 있었고, GFH의 비표면적은 257 m2·g-1으로 126~136 m2·g-1인 ABA-500 보다 매우 높은 값을 보였다. 세 종류의 흡착제로 비소 흡착 회분식 실험을 진행했으며, 반응시간과 초기 비소농도, pH 및 온도에 따라 흡착효율을 비교했다. 동적흡착실험 결과 GFH, ABA-500(granule), ABA-500(3mm) 순으로 빠르게 비소를 흡착했고 세 흡착제 모두 유사 2차 반응속도 모델을 따르는 것으로 나타났다. 또한 세 흡착제 모두 낮은 pH와 높은 온도에서 비소 제거율이 증가했으며, GFH가 가장 뛰어난 비소 흡착능을 보였다. 흡착제 ABA-500(granule)과 GFH를 초기 농도에 따라 1시간 반응시킨 경우 0.2와 1 mg·g-1 이하 조건에서 비소를 국내 음용수 기준치 이하로 제거할 수 있었다. 따라서 정화대상지의 비소 오염 정도가 낮은 경우 경제성을 고려해 ABA-500(granule)을 흡착매질로 적용할 수 있을 것으로 기대된다.